MACROECONOMIA DO DESENVOLVIMENTO: UMA PERSPECTIVA KEYNESIANA, JOSÉ LUÍS DA COSTA OREIRO - Costa da Silva, Guilherme Jonas (Investigación Económica, 2023)
In Brazil, Professor José Luís Oreiro is considered one of the most talented and productive Keynesian economists of his generation. Prof. Oreiro was hired by the Department of Economics at the Federal University of Paraná in 2003, when I came into touch with some of the theories organized in this book. This book written by Oreiro presents the debate around development macroeconomics from a Keynesian perspective, which is a new and particularly important topic for those who wish to understand a little more about macroeconomics, growth, and economic development. The main contribution of the book Macroeconomia do Desenvolvimento: Uma Perspectiva Keynesiana is to demonstrate that, for Keynesian theory, macroeconomic policies traditionally more related to business cycles, have effects on long run growth and development. Short run policies affect the long run, because aggregate demand is considered the engine of long-run growth (Keynes, 1982)...